The Dynamic Wheel-Rail Contact Stresses for Wagon on Various Tracks - Xia, F.; Cole, C.; Wolfs, Peter (Elsevier B.V, 2008)
The maximal stress and tangential surface forces at the wheel-rail contact elliptic area are affected by the wheel-rail contact dynamic load and creepages. Dynamic wheel load is related to the wagon dynamic system, track and wheel-rail interaction. Creepages are related to the motion of wheelset and wheel-rail contact parameters. The paper presents an analysis of the effects of creepages on wheel-rail contact forces. A complete Australia wagon with three-piece bogies was modelled and various tracks were selected for the simulation of dynamic wheel-rail contact stresses. The results show that the maximal normal wheel-rail contact stresses is under 1600 MPa in a range of conditions of typical normal operation.